Determination of long-tailed macaque's (Macaca fascicularis) harvesting quotas based on demographic parameters - YANTO SANTOSA; KUSMARDIASTUTI KUSMARDIASTUTI; AGUS PRIYONO KARTONO; DEDE AULIA RAHMAN (Biodiversitas Journal of Biological Diversity, 2012)
Santosa Y, Kusmardiastuti, Kartono AP, Rahman DA. 2012. Determination of long-tailed macaque's (Macaca fascicularis) harvesting quotas based on demographic parameters. Biodiversitas 13: 79-85. Harvesting quota of long-tailed macaques for breeding purpose should be set up based on demographic parameters. The objectives of this research were to determine demographic parameters affecting the set up of harvesting quota and the sustainable harvesting quotas of long-tailed macaque in Indonesia. This study was expected to provide useful information for consideration of setting up harvesting quotas for long-tailed macaque in Indonesia. This study was conducted in November 2009-Januari 2010 using the equation of Q = Nt-MVP. The results showed varied harvesting quotas for different age classes of long-tailed macaque with an average number of 5 for infant males, 3 for infant females, 5 for juvenile males, 4 for juvenile females, 6 for sub-adult males, 8 for sub-adult females and 2 for adult males. The dominant variable determining quota was survival rate.